Pengaruh Leadership Style dan Organizational Culture terhadap Productivity Of Employee di Koperasi Simpan Pinjam-Sejahtera Bersama (KSP-SB) Cabang Sukabumi - Umban Jaya; Ai Kartini (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2021)
This research was conducted at the Sukabumi Branch of the Savings and Loans Cooperative and the Prosperous Cooperative (KSP-SB) with a full address on Jl. R.E Martadinata No. 62 B Cikole Village, Cikole District, Sukabumi City- (0266) 211867, This study runs from January 2018 to completion.The purpose of this study was to determine the effect of leadership style (X1) and organizational culture (X2) on productivity of employee (Y). The types and sources of data used in this study consisted of primary data and secondary data with a total sample of 30 people. Sampling is done using population sampling method. Technical quality testing tools include testing validity and reliability, classical assumptions, and data analysis techniques using descriptive and correlation analysis. Whereas to determine the effect of independent variables (X) on the dependent variable (Y), multiple linear regression analysis was used which included the t test and F test with the help of SPSS version 16.0. Based on the results of the partial test (t test), it can be seen that the leadership style variable has a positive but not significant effect on productivity of employee, while the organizational culture variable has a positive and significant influence on productivity of employee. Based on the results of the Simultaneous Test (Test F) it is known that the variables of leadership style and organizational culture together have a significant influence on productivity of employee at the Sukabumi Branch of the Joint Savings and Loan Cooperative (KSP-SB).